Pengaruh Online Customer Review, Online Customer Rating dan Persepsi Harga terhadap Keputusan Pembelian pada Mahasiswa Pengguna Aplikasi Shopee di Universitas Hindu Indonesia (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
There is attention and findings regarding problems regarding online customer reviews, online customer ratings and price perceptions in an effort to improve and increase employee performance in accordance with the aim of this research to determine the influence of consumer purchasing decisions in accordance with the aim of this research, namely to determine the influence of online customer reviews, online customer rating and price perception on consumer purchasing decisions among students using the Shopee application at the Indonesian Hindu University. The sample in this study was 100 respondents with a sampling technique using purposive sampling. The analysis technique used is multiple linear regression analysis. The research results show that online customer reviews, online customer ratings and price perceptions have a positive and significant influence partially and simultaneously on purchasing decisions. Suggestions that can be given to companies include 1) It is hoped that companies will require consumers to provide reviews by including photos or videos of the items they have purchased. 2) It is hoped that sellers need to pay attention and prioritize product quality and improve the quality of service and delivery of goods so that in the future there will be no bad ratings. 3) It is hoped that sellers will pay attention to price because it is the first thing consumers see. 4) It is hoped that sellers use original product photos on every item sold so that consumers are not disappointed with the products they have purchased and provide positive recommendations to other consumers.